Price Discovery Mechanism in the Indian Agricultural Commodity Futures Market – An Empirical Analysis - Lethesh, M.; Viswanatha Reddy, C. (Indian Journal of Finance, 2023)
Purpose : In India, commodity futures markets are the best alternative to the securities markets because of their familiarity with risk hedging. It makes sense that information regarding futures contract pricing is provided by the way prices behave in the futures market analysis. The relationship between futures contract prices and commodities spot market prices is made clearer by the price discovery process. The current study provided an example of how 10 agricultural prices were determined. Methodology : The present study adopted exploratory and causal research designs based on cash and near-month futures contract prices of the selected agricultural commodities chosen through the purposive sampling method. The study used the augmented Dickey–Fuller (ADF) test, co-integration analysis, Granger causality test, and vector error correction model (VECM) to comprehend the efficiency of the price discovery mechanism of agricultural commodity futures markets in India. Findings : The study’s statistical findings demonstrated that the cash and futures markets possessed comparable proficiency in terms of price discovery methods for chana, jeera, maize, moong, and soybean. However, the cash market drove the futures market for coriander and cotton cake, and the futures market directed the spot market for price discovery for barley, turmeric, and wheat. Practical Implications : The study’s findings will be beneficial to market participants in adopting a range of arbitrage and trading techniques as well as to policymakers in confirming the consistency of both spot and futures markets, given the growing state of the commodity futures market in India. Originality : The novelty of the present study is the selection of sample agricultural commodities that were actively trading and highly liquid in the commodities market using the purposive sampling method. The statistical results have highlighted the effectiveness of price discovery in spot and futures markets for all the commodities covered in the study. Traders thus profited from the study’s conclusions when they periodically framed their trading strategies.